2008
DOI: 10.1111/j.1349-7006.2008.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization and quantification of the anticancer agent, cis‐diamminedichloro‐platinum(II), in human lung cancer cells using in‐air microparticle‐induced X‐ray emission analysis

Abstract: The authors designed an elemental analysis system using an ion microbeam combined with a microparticle-induced X-ray emission (micro-PIXE) method for the analysis of biomedical samples in air with a spatial resolution of 1 μ μ μ μm (in-air micro-PIXE system). This system was used to develop an imaging and quantification method for intracellular cis-diamminedichloro-platinum(II) (CDDP) in a human lung cancer cell line. A human lung adenocarcinoma cell line, A549, was cultured and nuclear labeling was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Proton microprobe analysis showed that platinum effectively reached the nucleus Review. Bio-metals imaging and speciation R. Ortega et al S651 of the cells exposed to cisplatin but with a low specificity (Moretto et al 1995;Ortega et al 1996;Mauthe et al 1998;Sakurai et al 2008). Trace element quantification in cisplatin-resistant cells also revealed a strong increase in the copper content (Ortega et al 1996), which can be linked to the expression of copper transport proteins in cisplatin-resistant cells (Ishida et al 2002).…”
Section: Examples Of Applicationmentioning
confidence: 99%
“…Proton microprobe analysis showed that platinum effectively reached the nucleus Review. Bio-metals imaging and speciation R. Ortega et al S651 of the cells exposed to cisplatin but with a low specificity (Moretto et al 1995;Ortega et al 1996;Mauthe et al 1998;Sakurai et al 2008). Trace element quantification in cisplatin-resistant cells also revealed a strong increase in the copper content (Ortega et al 1996), which can be linked to the expression of copper transport proteins in cisplatin-resistant cells (Ishida et al 2002).…”
Section: Examples Of Applicationmentioning
confidence: 99%
“…An example is the application of this method in (bio)imaging intracellular cis-diamminedichloridoplatinum (CDDP) in a human lung cancer cell line (Sakurai et al, 2008). The results of this research show that accumulation of cis-platin in human lung cancer cells increased with drug exposure time.…”
Section: Application Of Pixe Methods In (Bio)imaging/mapping Elements mentioning
confidence: 94%
“…The results of this research show that accumulation of cis-platin in human lung cancer cells increased with drug exposure time. Because the concentration of this complex is very high and most cells lose viability after 24 h exposure to CDDP, the uptake of CDDP in the cells must occur by a passive mechanism under no physiological condition (Sakurai et al, 2008). (Bio)imaging studies on toxic heavy metals can be very important from a toxicology point of view.…”
Section: Application Of Pixe Methods In (Bio)imaging/mapping Elements mentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray fluorescence spectrometry has been used for obtain the spatial elemental map for the biological samples. 7,8 In this study, we used the particle induced X-ray emission analysis technique with micron-sized probe beams (µ-PIXE analysis) for quantification of platinum in single cells. The aim of this study was to evaluate the kinetics of the cisplatin micelle by measuring the uptake and the intra-cellular distribution of platinum by using µ-PIXE analysis.…”
Section: Introductionmentioning
confidence: 99%